A BPMN solution for chaining OGC services to quality assure location-based crowdsourced data. (February 2016) - Meek, Sam; Jackson, Mike; Leibovici, Didier G
Abstract: The Open Geospatial Consortium (OGC) Web Processing Service (WPS) standard enables access to a centralized repository of processes and services from compliant clients. A crucial part of the standard includes the provision to chain disparate processes and services to form a reusable workflow. To date this has been realized by methods such as embedding XML requests, using Business Process Execution Language (BPEL) engines and other external orchestration engines. Although these allow the user to define tasks and data artifacts as web services, they are often considered inflexible and complicated, often due to vendor specific solutions and inaccessible documentation. This paper introduces a new method of flexible service chaining using the standard Business Process Markup Notation (BPMN). A prototype system has been developed upon an existing open source BPMN suite to illustrate the advantages of the approach. The motivation for the software design is qualification of crowdsourced data for use in policy-making. The software is tested as part of a project that seeks to qualify, assure, and add value to crowdsourced data in a biological monitoring use case. Highlights: A prototype system for chaining OGC services is built using open source software. The system uses the functions of an OGC Service to expose workflow tasks. The workflow engine composes the http requests for each WPS and carries the results. Motivation is to quality assure crowdsourced data in a Citizen Observatory context.